Women’s agency in water governance:: lessons from the water and health nexus in Armenia and Ukraine (Sustainability in Debate, 2017)
Water security is a global challenge and a collective responsibility for all humanity. The way in which people are affected by or impact on water availability, quality and management is quite heterogeneous; and it has a distinct gender dimension. Social relations between women and men result in gendered roles that vary between social strata, cultures, ethnicities and generations. In traditional societies women are often the water seekers and carriers, while their involvement in decision-making is limited. This article focuses on women’s agency for sustainable use and management of water resources. It provides examples from Armenia and Ukraine demonstrating women’s civil society contributions to the development and implementation of the Protocol on Water and Health. It shows how women’s meaningful participation has made a difference, and sheds light on the preconditions for meaningful involvement of women’s civil society in processes of water cooperation and participatory water governance.